Pelatihan Penggunaan Repositori Arsip Digital Manuskrip Bagi Pegawai Museum Sang Nila Utama - Nining Sudiar; Iik Idayanti; Hadira Latiar (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
The current target community service partners are Sang Nila Utama Museum employees. This service is a continuation of research activities regarding the design of the manuscript repository for the Sang Nila Utama Museum collection. Currently, all manuscript collections have been recorded, however, the public still cannot access these digital manuscripts easily, this is because the person in charge of the museum and their employees do not yet have an understanding of the advantages of using a repository. Seeing these conditions, it is necessary to conduct training for employees regarding the use of the repository. The purpose of this activity, namely (1) to provide knowledge to employees about the repository; (2) to Employees have knowledge and understanding of the use of repository services. In order to achieve the above objectives, it is necessary to hold activities, including (1) Counseling related to the museum collection repository and manuscripts; (2) brief training on using the repository service. Participants who took part in the activity totaled 5 people. The results of the service show that at first, the participants did not have an understanding of repository services, but after counseling, the participants understood the meaning and function of repository services. It is hoped that in the future, this repository service can be applied to all collections, not only manuscripts but other museum collection objects.